Интерференция как препятствующий фактор в изучении иностранных языков - Воробьёва, М.В.; Евтихова, И.М. (Культура народов Причерноморья, 2013)
Статья посвящена актуальной на сегодняшний день проблеме фонетической
интерференции как следствию языковых контактов. В статье изложены особенности фонетического
строя русского, украинского, немецкого и английского языков. Проведенный анализ показал, что
изучаемые явления имеют ряд как общих, так и отличительных фонетических черт. В данной статье
предпринята попытка раскрыть основные причины возникновения интерференции. Произведен анализ
литературы по данной теме. Выявлены основные причины, приводящие к интерференции в
иностранных языках. Стаття присвячена актуальній на сьогоднішній день проблемі фонетичної інтерференції, як
наслідку мовних контактів. У статті викладено особливості фонетичного ладу російської, української,
німецької та англійської мов. Проведений аналіз показав, що досліджувані явища мають цілу низку як
загальних, так і відмінних фонетичних якостей. У даній статті зроблена спроба розкрити основні
причини виникнення інтерференції. Здійснено аналіз навукової літератури з даної теми. Виявлені
основні фонетичні особливості, що призводять до інтерференції в іноземній мові. The article is devoted to the issue – the problem of phonetic interference following from language
contacts. The article describes peculiarities of the phonetic system of the Russian, Ukrainian, German and
English languages. The analysis showed that the investigated phenomena have a number of both common and
distinctive phonetic features. This paper attempts to reveal the main causes of interference. The article gives
different interpretations of the notion “interference”. The authors of this article adopt the following definition of
the notion of “interference”. Interference means cases of deviation from the norms of any of the languages, i.e.
interference is a result of language contacts (W. Weinrich “Monolingualism and multilingualism”). The
literature analysis on this subject is made. Phonetic interference problems have always attracted the attention of
linguists. This problem is considered by such scholars as W. Weinrich, L. Szczerba, M. Schuchardt and E.
Haugen.
The paper indentified the major reasons leading to interference in foreign languages. Linguistic causes that lead
to interference are the differences and similarities in language systems of contacting languages. This article
provides ways to reduce the impact of phonetic interference in second language learning. The topic of the article
is actual and research in this field is promising.